Virtual Simulation as a Teaching Strategy for Basic Life Support in Nursing Education: A Systematic Review - I Putu Juni Andika; Seftiani Utami; Dian Putranto (Universitas STRADA Indonesia, 2025)
Background: Certain training programs, like Basic Life Support training, must change to comply with the new social and physical distancing policies. Health care workers, including nursing students, may benefit from Virtual Simulation, instruction, in order to help them meet the Basic Life Suppport competencies. Therefore, innovation in learning methods through virtual simulation is needed to provide interactive and realistic learning experiences, as well as to enhance students’ knowledge, clinical skills, critical thinking, and self-confidence before entering clinical practice.